Justice, Equality, and Indonesian Labor Law: Navigating Humanitarian Challenges in the Workplace - Nurhayati, Tri; Ismoyoputro, Raden Lungid (Universitas Islam Negeri Walisongo Semarang, 2024)
This article aims to explore the challenges increasing number of workers leads to a decrease in workers' bargaining power, which in turn raises the potential for abuse by employers. The government, as the policymaker, is expected to protect workers and guarantee Human Rights as stipulated in the 1945 Constitution. This research adopts a non-doctrinal approach with a normative perspective, utilizing documentation and literature studies as data sources. The research findings indicate that the issues of equality and justice in Indonesian labor law have not yet been fully realized. Changes in norms in various aspects of labor law, from Law Number 13 of 2013 concerning Manpower to Law Number 6 of 2023 concerning the Determination of Government Regulations replacing Law Number 2 of 2022 concerning Copyright, further highlight the disparities faced by workers, who are often subject to oppression in their relationships with employers. Several forms of injustice that still frequently occur include discrimination in recruitment processes and treatment in the workplace, harassment, intimidation, labor exploitation, violations of Health and Safety (K3) norms, injustice in the wage system, and the fulfillment of workers' rights in termination of employment.Artikel ini bertujuan mengkaji tantangan peningkatan jumlah tenaga kerja menyebabkan posisi tawar pekerja menjadi lebih lemah, yang pada akhirnya meningkatkan kemungkinan terjadinya penyalahgunaan oleh pengusaha. Pemerintah diharapkan dapat melindungi hak pekerja dan memastikan pemenuhan Hak Asasi Manusia sesuai dengan UUD 1945. Penelitian ini memakai pendekatan normatif non-doktrinal dengan memanfaatkan studi dokumentasi dan literatur sebagai sumber data. Hasil penelitian mengindikasikan bahwa prinsip kesetaraan dan keadilan dalam Hukum Ketenagakerjaan di Indonesia masih belum sepenuhnya terlaksana. Perubahan norma dalam aspek ketenagakerjaan dari Undang-Undang Nomor 13 Tahun 2013 ke Undang-Undang Nomor 6 Tahun 2023 menunjukkan adanya ketimpangan yang menyebabkan pekerja sering menjadi korban penindasan dalam hubungan kerja dengan pengusaha. Beberapa bentuk ketidakadilan yang masih sering terjadi meliputi diskriminasi dalam proses rekrutmen dan perlakuan di tempat kerja, pelecehan, intimidasi, eksploitasi tenaga kerja, pelanggaran norma Kesehatan dan Keselamatan Kerja (K3), ketidakadilan dalam sistem pengupahan, serta pelanggaran hak pekerja yang mengalami PHK.